Towards a headline-based deception detection approach for data veracity in online digital news - Eembi @ Jamil, Normala Che; Ishak, Iskandar; Sidi, Fatimah; Affendey, Lilly Suriani (Faculty of Electronic and Computer Engineering, Universiti Teknikal Malaysia Melaka, 2017)
Since its existence in 1990's, online news has been the major source of news content for news readers. Unfortunately, based on a number of findings, readers tend to judge on certain event based on the news headlines rather than its contents. With the advancement of mobile and web technologies, it is easier to spread news to others and this unhealthy habits can cause negative impacts towards individuals, organizations or nations that are victimized by the news. This paper proposes a framework to detect deceptive online news based on the news headlines. By having an accurate detection upon deceptive news based on its content, it can assist readers to identify misleading news and to help them to find relevant news for their source of information.